Physical And Sensory Characteristics Of Emulsion Drinks Red Palm Oil - Devi Silsia; Liza Bunaiyah; Budiyanto Budiyanto (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2021)
Red palm oil contains carotenoids (β, α, ϒ-carotene) so that it has the potential to be developed into a healthy oil. This study aims to obtain physical characteristics (viscosity and stability) and sensory of red palm oil emulsion drink at various concentrations of the addition of CMC and mango flavor. This study used a completely randomized design (CRD) with 2 factors, namely the CMC concentration (0.5%, 0.75% and 1%) and the mango flavor concentration (1.5% and 2%). Red palm oil emulsion drink has a viscosity of 137.93 - 314.92 cP and stability of 77.66 - 94.06%. Sensory score for color 3.44 - 3.80, aroma 3.0 - 3.53, taste 2.72 - 3.00 and viscosity 3.16 -3.32. The higher the CMC concentration and the added manga flavor, the higher the viscosity and stability as well as the sensor score.